A model-free damage identification method for flexural structures using dynamic measurements from distributed long-gage macro-strain sensors. (September 2014) - Tang, Yongsheng; Wu, Zhishen; Yang, Caiqian; Wu, Gang; Wan, Chunfeng
A damage identifying algorithm, named modal macro-strain vector, has been verified as efficient to locate local damages for flexural structures, with modal parameters directly extracted from the dynamic macro-strain measurements. However, the basic relation between the change in modal macro-strain vector and damage severity has not been established yet. In this article, a model-free damage identification method is proposed based on the modal macro-strain vector method to implement both damage location and quantification. In this method, one assumption is first proposed that the normalized modal macro-bending-moment is constant, as proved by the simulations. Then, damage quantification is performed with the combination of the spatial parameter of neutral axis and normalized modal macro-strain vector. In view of these, different finite element beam models are simulated with several damage cases for each specimen to verify the method. Simulation results show that the damage severity can be evaluated with a high accuracy with the proposed method. As a result, the efficiency of the method is verified through the experiments of a steel beam in the laboratory. Therefore, the proposed system is proved to be effective and useful for structural health monitoring.